Investigating the Impact of Sample Preparation on Mass Spectrometry-Based Drug-To-Antibody Ratio Determination for Cysteine- and Lysine-Linked Antibody–Drug Conjugates - Malin Källsten (Antibodies, 2020)
Antibody–drug conjugates (ADCs) are heterogeneous biotherapeutics and differ vastly in their physicochemical properties depending on their design. The number of small drug molecules covalently attached to each antibody molecule is commonly referred to as the drug-to-antibody ratio (DAR). Established analytical protocols for mass spectrometry (MS)-investigation of antibodies and ADCs often require sample treatment such as desalting or interchain disulfide bond reduction prior to analysis. Herein, the impact of the desalting and reduction steps—as well as the sample concentration and elapsed time between synthesis and analysis of DAR-values (as acquired by reversed phase liquid chromatography MS (RPLC–MS))—was investigated. It was found that the apparent DAR-values could fluctuate by up to 0.6 DAR units due to changes in the sample preparation workflow. For methods involving disulfide reduction by means of dithiothreitol (DTT), an acidic quench is recommended in order to increase DAR reliability. Furthermore, the addition of a desalting step was shown to benefit the ionization efficiencies in RPLC–MS. Finally, in the case of delayed analyses, samples can be stored at four degrees Celsius for up to one week but are better stored at −20 °C for longer periods of time. In conclusion, the results demonstrate that commonly used sample preparation procedures and storage conditions themselves may impact MS-derived DAR-values, which should be taken into account when evaluating analytical procedures.